Hubungan Kecepatan Dan Power Otot Tungkai Terhadap Kemampuan Lompat Jauh Siswa Putri Kelas V Upt Sd Negeri 12 Turatea - Andi Mutmainnah; Alif Aryadi Hardi; afitriani (Universitas Mataram, 2026)
This research is motivated by the observation that during long jump learning, several students had not maximized their approach run and were inaccurate during the take-off. The objective of this research is to determine the relationship between running speed and leg power with the long jump ability of 5th-grade female students at UPT SD Negeri 12 Turatea. This research is a correlational study. The research population consisted of 30 female students in Grade V at UPT SD Negeri 12 Turatea. The research instruments were the sprint test, standing broad jump test, sit and reach test, and long jump skill test. The data collection technique utilized test and measurement techniques. Data analysis used the Pearson Product Moment Correlation technique. The results of the research show: (1) There is a significant relationship between running speed and the long jump ability of 5th-grade female students at UPT SD Negeri 12 Turatea, where the r-calculated value